Pengaruh Leadership Transformasional terhadap Motivasi Kerja Guru di Sekolah Islam - Kotimah, Khusnul; Rindaningsih, Ida (TSAQOFAH, 2025)
The influence of transformational leadership is a very important aspect in the science of Islamic education management, especially on teacher work motivation in Islamic schools. However, not all teachers have high work motivation, teacher dissatisfaction is also often caused by a lack of support from the principal and the lack of solidity of the work team at school. So an effective leadership approach is needed to encourage their enthusiasm and dedication. By integrating Islamic values in leadership such as justice, trust, and responsibility, transformational leadership is able to increase teachers' work motivation, both professionally and spiritually. Through the literature review method from journals, articles, and others, this research can deeply analyze the influence of transformational leadership on teacher work motivation in Islamic schools. The results showed that transformational leadership has a significant influence on teachers' work motivation. Teachers led by this style tend to be more motivated, proactive, and satisfied with their work. External factors, such as adequate work facilities and organizational support, were also found to support the successful implementation of this leadership style. therefore, well-implemented transformational leadership in Islamic schools not only improves teacher performance but also contributes to the overall achievement of Islamic education goals.